Effect of behavior modification combined with health belief model education on adherence to skin moisturizing care in patients with psoriasis vulgaris - Luping Tian; Yuhua Weng; Aiqing Xu; Yuefang Chen; Juping Tang (Scientific Reports)
Abstract To examine the impact of an educational approach incorporating behavioral modification and the Health Belief Model on the adherence to skin moisturizing care, itch severity, self-efficacy, and quality of life among individuals diagnosed with psoriasis vulgaris. A study involving 108 psoriasis vulgaris patients (November 2022–October 2023) utilized random allocation to form experimental and control groups. The control group received standard care, including medication guidance, general health education, and basic nursing support. In contrast, the experimental group underwent an enhanced intervention that combined behavior modification techniques and education based on the Health Belief Model. This included biweekly educational sessions, personalized behavioral assessments, and self-monitoring tools like self-supervision cards, which were not provided to the control group. Assessments pre- and post-intervention measured itchiness, self-efficacy, and quality of life. Comparative analyses included pruritus, self-efficacy, adherence, and quality of life using various scales. The study aimed to evaluate the impact of combined interventions on these parameters in psoriasis patients. Following the intervention, both groups exhibited improvements in itching degree, itching frequency, and affected areas compared to pre-intervention levels, with the experimental group showing superior outcomes over the control group. GSES scores in both groups increased post-intervention, with the experimental group surpassing the control group. Both groups demonstrated enhanced scores post-intervention across various aspects, including forgetting to use medication, willingness to use medication, influencing factors, medication timing, frequency, and quality of life (assessed by DLQI). Furthermore, MORISKY scores for medication timing, frequency, and self-discontinuation decreased in both groups post-intervention, with the experimental group recording lower scores than the control group. DLQI scores for symptom feelings, daily life, leisure and recreation, work and study, interpersonal relationships, and treatment were reduced in both groups after the intervention, with the experimental group showing lower scores than the control group. Combining behavior modification and health belief model education effectively improves adherence to skincare, relieves itching in psoriasis patients, and enhances self-efficacy and overall quality of life.